Debt Relief, Additionality, and Aid Allocation in Low Income Countries - Powell, Robert (IMF Working Papers; Working Paper ;, 2003)
This paper models the resource implications of debt relief provided to low-income countries (LICs). Obtaining debt relief does not necessarily lead to individual aid-dependent countries receiving more overall resources from the donor community. Preliminary cross-section estimates suggest that debt relief provided to low-income countries in the period 1996 2000 neither crowded out other non-debt relief-related aid flows to the debtors concerned nor created significant extra net resources for those countries. While it is too early to fully assess the resource implications of the enhanced HIPC Initiative, this paper provides a possible approach to such an evaluation.